Covalent adducts of DNA and the nonprotein chromophore of neocarzinostatin contain a modified deoxyribose. - Povirk, L F (1982)
When the nonprotein chromophore of neocarzinostatin was allowed to react with either calf thymus DNA or poly(dA-dT) . poly(dA-dT) in the presence of 2-mercaptoethanol and the DNA was precipitated with ethanol, 5% of the fluorescence attributable to the naphthalene rings of the chromophore coprecipitated with the DNA. Most of this fluorescence remained attached to DNA through successive reprecipitations, suggesting formation of covalent adducts between chromophore and DNA. Enzymatically digested poly(dA-dT) . poly(dA-dT)-chromophore adduct contained, in addition to deoxyadenosine and thymidine, several highly fluorescent hydrophobic products, separable by reverse-phase chromatography, all of which contained both adenine and thymine radiolabel, as well as chromophore radiolabel. One such product consistently had twice as much thymine as adenine, suggesting a structure chromophore-d(TpApT), in which the attached chromophore rendered both phosphodiester bonds refractory to endonuclease S1. This adduct fragment was completely hydrolyzed at pH 12, releasing adenine, 3'-dTMP, and 5'-dTMP. At pH 7, the adduct fragment slowly released chromophore and 3'-dTMP with parallel kinetics, leaving a modified d(ApT), which was cleaved by snake venom phosphodiesterase to yield 5'-dTMP and a modified deoxyadenosine. These hydrolysis patterns are unlike those of any previously characterized base or phosphotriester DNA adduct but rather indicate an altered deoxyadenosine sugar. The formation of adducts containing a modified deoxyribose suggests that deoxyribose may be the site of covalent chromophore attachment. Alteration of this same site, possibly the 5'-carbon of the sugar moiety, may account for the extreme lability of the phosphodiester bond.